"Orthogonality" in Learning and Assessment. Issue 165 (March 2014) - Leslie, David
Abstract : This chapter proposes a simple framework, "orthogonality, " to help clarify what stakeholders think about learning in college, how we assess outcomes, and how clear assessment methods might help increase confidence in returns on investment.